2013
DOI: 10.1152/japplphysiol.00075.2013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating microRNAs levels with exercise modality

Abstract: Here, we studied muscle-specific and muscle-related miRNAs in plasma of exercising humans. Our aim was to determine whether they are affected by eccentric and/or concentric exercise modes and could be biomarkers of muscle injuries or possible signaling molecules. On two separate days, nine healthy subjects randomly performed two 30-min walking exercises, one downhill (high eccentric component) and one uphill (high concentric component). Perceived exertion and heart rate were higher during the uphill exercise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 35 publications
10
113
5
1
Order By: Relevance
“…The mechanism by which exercise restores these microRNAs remains to be investigated. However, it has been shown in humans that even short bouts of exercise can alter the microRNA profile of serum (8,65). It should be noted that exercise interventions in founders (HE and HCE) were previously shown to result in the greatest improvements to embryo development (38) and insulin sensitivity in female offspring at 9 wk of age in this study.…”
Section: X-linked Sperm Micrornas As Molecular Mediators Of Paternal mentioning
confidence: 56%
“…The mechanism by which exercise restores these microRNAs remains to be investigated. However, it has been shown in humans that even short bouts of exercise can alter the microRNA profile of serum (8,65). It should be noted that exercise interventions in founders (HE and HCE) were previously shown to result in the greatest improvements to embryo development (38) and insulin sensitivity in female offspring at 9 wk of age in this study.…”
Section: X-linked Sperm Micrornas As Molecular Mediators Of Paternal mentioning
confidence: 56%
“…It is possible that there are mechanisms of preliminary miRNA concentration/accumulation by recipient cells. After the damage of muscle fibers due to physical exercise the levels of muscle-specific miR-1 and miR-133 was significantly elevated in the plasma, but became already normal after several hours (Uhlemann et al, 2012;Banzet et al, 2013). This observation indicates the existence of mechanisms of rapid utilization of extracellular miRISC, so that they are present in the bloodstream much less time than might be expected based on their stability in vitro (Turchinovich et al, 2011).…”
Section: сEll-cell Communication Via Circulating Micrornasmentioning
confidence: 89%
“…The strongest evidence in favor of non-selective release of AGOassociated c-miRNA is the fact that miRNA content in cell culture media correlates with the level of cell death (Turchinovich et al, 2011). Likewise, many in vivo studies have shown that damage of certain organs leads to an increase in the tissue-specific miRNA levels in the circulation (Laterza et al, 2009;Corsten et al, 2010;Zhang et al, 2010;Uhlemann et al, 2012;Banzet et al, 2013;Akat et al, 2014). It is feasible, that the majority of these miRNAs is EVfree and associated purely with AGO proteins.…”
Section: Extracellular Mirnas and Pathways Of Their Secretionmentioning
confidence: 99%
“…Ulheman encontró que el ejercicio de resistencia muscular anaeróbico (cargas excéntricas) generaba incremento de miR-133 (específico de músculo esquelético) 36 . Banzet y cols., también identificaron elevación de miRNAs específicos de músculo esquelético (hsa-miR-1, miR-133a, miR-133b y miR-208b) con ejercicio muscular excéntrico (caminata cuesta abajo), el cual se asocia a daño muscular 37 . En contraste, Sawada y cols., no reportaron incremento de los mio-miRNAs en respuesta a un ejercicio de resistencia muscular anaeróbico (levantamiento de pesas con piernas) 38 (Tabla 1).…”
Section: Mecanismos De Liberación De Micrornas Circulantes Durante Ejunclassified